Steve & Barry's : to save or not to save? - Mazzeo, Michael, (SAGE Knowledge. Cases., 2017)
Steve & Barry's grew rapidly in the mid-2000s, transitioning from a chain of small stores selling inexpensive collegiate-branded merchandise near university campuses into a $1 billion mall-based giant selling a wide variety of low-priced, celebrity-endorsed apparel. While the company had a wide following, elements of its growth strategy potentially exacerbated by economic conditions contributed to its quick downfall. By 2008 Steve & Barry's had declared bankruptcy, and various private equity firms were investigating whether some or all of the company should be saved. This requires analyzing the underlying business strategy pursued by Steve & Barry's before and after its growth phase and specifically diagnosing the explanations for its failure.